2014
DOI: 10.3390/e16020770
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetric Chaos-Based Image Cipher with an Improved Bit-Level Permutation Strategy

Abstract: Abstract:Very recently, several chaos-based image ciphers using a bit-level permutation have been suggested and shown promising results. Due to the diffusion effect introduced in the permutation stage, the workload of the time-consuming diffusion stage is reduced, and hence the performance of the cryptosystem is improved. In this paper, a symmetric chaosbased image cipher with a 3D cat map-based spatial bit-level permutation strategy is proposed. Compared with those recently proposed bit-level permutation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…For example, the basic unit of an image can also be represented as bit (for example, a pixel value 54 can be represented as "00110110"). Some bit-level image encryption algorithms can be found in [22][23][24][25], which can play a permutation and diffusion effect simultaneously by a bit-level permutation. Zhu et al in [22] proposed an image cryptosystem employing the 2D Arnold map for bit-level permutation, and this cryptosystem can obtain diffusion effect and save some encryption time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the basic unit of an image can also be represented as bit (for example, a pixel value 54 can be represented as "00110110"). Some bit-level image encryption algorithms can be found in [22][23][24][25], which can play a permutation and diffusion effect simultaneously by a bit-level permutation. Zhu et al in [22] proposed an image cryptosystem employing the 2D Arnold map for bit-level permutation, and this cryptosystem can obtain diffusion effect and save some encryption time.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the encryption time is substantially reduced. In [4][5][6][7], schemes with certain diffusion effect introduced in the permutation stage are proposed. As the pixel value mixing effect is contributed by both stages, the number of iteration rounds required by the diffusion procedure is reduced, and hence the performance of the cryptosystem is improved.…”
mentioning
confidence: 99%
“…Unfortunately, the redundant iteration operations downgrade the efficiency of the cryptosystem to some extent. In [16], the value of each keystream element is dynamically altered according to the plain-pixel values during the substitution process.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results have demonstrated that their scheme takes one round of permutation and two rounds of substitution to obtain a satisfactory diffusion effect. In [16,[21][22][23], chaos-based image ciphers using a bit-level permutation were suggested. Owing to the substitution effect introduced in the permutation stage, the number of iteration rounds required by the time-consuming substitution procedure is reduced, and hence a shorter encryption time is needed.…”
Section: Introductionmentioning
confidence: 99%